"Integrated thinking and reporting" towards sustainable business models: a concise bibliometric analysis. Issue 4 (14th July 2020) - Di Vaio, Assunta; Syriopoulos, Theodore; Alvino, Federico; Palladino, Rosa
Abstract : Purpose: This paper aims to provide a thorough and systematic overview of the academic literature focusing on the role of integrated reporting (IR) and integrated thinking (IT) in achieving sustainable business models (SBMs). The paper discusses whether the incorporation of newer IR systems can facilitate the integration of processes, as well as a better allocation of resources and capital to create long-term value, according to a circular approach. Design/methodology/approach: Based on a database containing 60 publications in English with a publication date from 1990 to 2019, a bibliometric analysis is conducted. Data on publications, journals, authors and citations are collected, verified, cross-checked and examined by applying bibliometric measures. Findings: Bibliometric analysis has identified that IR and IT have determined an evolution in the way companies communicate and create value, facilitating the integration of processes and a better allocation of resources and capital. However, market practice still perceives them as simple reporting tools to meet stakeholders' needs rather than as critical corporate governance tools. Research limitations/implications: This study highlights key issues in the past literature on IR and IT to meet SDGs, contributing also to the identification of critical difficulties that companies encounter in attempting to attain sustainable goals. Originality/value: This document contributes to the existing literature on IR, IT and SBMs through a systematic review of the literature on these topics along with the sustainable development goals perspective. The study, furthermore, attempts to assess the role that the relevant literature attributes to IR and IT in the SBMs architecture.